2009
DOI: 10.1089/ten.tea.2008.0253
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic Differentiation of Adipose-Derived Adult Stem Cells by a Porous Scaffold Derived from Native Articular Cartilage Extracellular Matrix

Abstract: Adipose-derived adult stem cells (ASCs) have the ability to differentiate into a chondrogenic phenotype in response to specific environmental signals such as growth factors or artificial biomaterial scaffolds. In this study, we examined the hypothesis that a porous scaffold derived exclusively from articular cartilage can induce chondrogenesis of ASCs. Human ASCs were seeded on porous scaffolds derived from adult porcine articular cartilage and cultured in standard medium without exogenous growth factors. Chon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
240
2
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(258 citation statements)
references
References 100 publications
10
240
2
6
Order By: Relevance
“…8 In vitro studies have shown that dehydrated, micronized allograft tissue promotes chondrogenesis. 9 Moreover, the BioCartilage technique uses the anabolic and anti-inflammatory benefits of PRP. Several trials have reported superior functional outcome and improved histologic scores when comparing PRPenhanced microfracture versus microfracture alone.…”
Section: Discussionmentioning
confidence: 99%
“…8 In vitro studies have shown that dehydrated, micronized allograft tissue promotes chondrogenesis. 9 Moreover, the BioCartilage technique uses the anabolic and anti-inflammatory benefits of PRP. Several trials have reported superior functional outcome and improved histologic scores when comparing PRPenhanced microfracture versus microfracture alone.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, it was shown that biomaterial scaffolds created solely from native extracellular matrix tissues also can control the differentiation of ASCs [16,21]. Using a porous scaffold derived exclusively from articular cartilage, chondrogenesis of ASCs in the absence of exogenous growth factors was examined.…”
Section: The Influence Of Biomaterials Scaffolds On Asc Chondrogenesismentioning
confidence: 99%
“…For example, after 4 weeks in culture, construct diffusivity decreased greater than 40% under chondrogenic conditions, and was associated with a net increase in the biosynthesis and retention of matrix macromolecules. [16] Volume…”
Section: Functional Properties Of Tissue-engineered Cartilage Construmentioning
confidence: 99%
“…6,7 Recently, more and more ECM-derived scaffolds have been examined and fabricated to offer a specific environment for cartilage repair or regeneration. [8][9][10][11][12] A previous study has revealed that cartilage extract matrix can promote the chondrogenesis of embryonic stem cells. 7 This suggests that articular cartilage ECM may play an important role in guiding the chondrogenic differentiation of MSCs.…”
mentioning
confidence: 99%